Integrated Development of Farm-forestry Plantations and Wood Based Industries - Lal, Plare (Indian Forester, 2004)
Farm forestry plantations, based on genetically improved planting stock and supported with improved package of practices, offer an economically attractive and environmentally safe option for much needed di versification of agriculture and growth of wood based industries. This paper highlights the need for integrated planning for promotion of farm-forestry and wood based industries as neither can grow in isolation. Integrated planning will also minimize periodical local demand and supply imbalances, cut down avoidable costs on transport of farm grown wood to far away factories and safeguard the legitimate interests of farmers and industries. Paper recommends specific policy initiatives for harnessing the full potential of technology based farm forestry plantations. The vast potential of farm forestry plantations for achieving self sufficiency in timber and wood-based products including newsprint and paper, thereby saving huge outflow of foreign exchange, is emphasized. Planned growth of farm forestry integrated with industries will create ample employment opportunities for the local people, enlarge the forest cover and ameliorate the environment and indirectly conserve the biodiversity rich natural forests by reducing biotic pressures on them.